Industrial espionage and technology transfer : Britain and France in the eighteenth century - Harris, John R., (Routledge, Taylor & Francis Group, 2017)
Britain and France were the leading industrial nations in 18th-century Europe. This book examines the rivalry which existed between the two nations and the methods used by France to obtain the skilled manpower and technology which had given Britain the edge - particularly in the new coal-based technologies. Despite the British Act of 1719 which outlawed industrial espionage and technology transfer, France continued to bring key industrial workers from Britain and to acquire British machinery and production methods. Drawing on a mass of unpublished archival material, this book investigates the nature and application of British laws and the involvement of some major British industrialists in these issues, and discusses the extent to which French espionage had any real success. In the process it presents an in-depth understanding of 18th-century economies, and the cultures and bureaucracies which were so important in shaping economic life. Above all, the late John Harris saw the history of industrial espionage as 'one means of restoring the thoughts and activities of human beings to the centre stage of industrial history'. These are the stories of individuals - Holkers, Trudaines, Wilkinsons, or Milnes - and their impact on the world.